KARMA IN OSCAR WILDE’S THE PICTURE OF DORIAN GRAY AND EMILY BRONTE’S WUTHERING HEIGHTS AS SEEN THROUGH THE LIVES OF DORIAN GRAY AND HEATHCLIFF = QUY LUẬT NHÂN QUẢ TRONG “BỨC CHÂN DUNG CỦA DORIAN GRAY” CỦA OSCAR WILDE VÀ “ĐỒI GIÓ HÚ” CỦA EMILY BRONTE THỂ HIỆN QUA CUỘC ĐỜI HAI NHÂN VẬT DORIAN GRAY VÀ HEATHCLIFF - Đoàn, Thị Gương (2020)
The Picture of Dorian Gray and Wuthering Heights are considered two of the masterpieces in English Literature. Up to now, in spite of several studies approaching the two novels in many different aspects such as love, feminism, art and morality, very little attention has been paid to karmic element in the tragic lives of two main characters – Dorian Gray and Heathcliff, as well as the effectiveness of using karma in presenting the main functions of literature. Based on the theory of karma from Buddhist perspective and from those of other religions, the writer has aimed at analyzing karma in Oscar Wilde’s The Picture of Dorian Gray and Emily Bronte’s Wuthering Heights as seen through the lives of the two main characters Dorian Gray and Heathcliff. After completing this study, the researcher has found out certain similarities and differences between these characters from karmic perspective. Even though they were influenced by completely different catalysts, their lives both strictly followed the law of cause and effect. They had to pay high price for their bad behaviours in the past. It can also be seen from the comparison and contrast between the two characters that karma plays a momentous role in delivering moral lessons to readers, which is always the focus of literature.